Physiology of calcium metabolism in kidneys (Ожирение и метаболизм, 2011)
Biologic functions of calcium include maintenance of skeletal integrity, signal transduction, cell permeability, excitation-secretion and excitation-contraction coupling and cell fertilization. There are various forms of calcium in the body: ionized, complexed and protein bound, and only two first forms can be filtered at the glomerulus and cross cell membranes. The present review covers the topics of physiology, regulation and pathogenesis of disturbances of renal calcium metabolism.